2020
DOI: 10.1002/slct.202003071
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Acid‐Base Sites of Solid Ba‐Zr Mixed Oxide Catalyst for Efficient Isomerization of Glucose to Fructose in Aqueous Medium

Abstract: Efficient and highly selective isomerization of glucose to fructose was achieved by using the inexpensive Ba−Zr mixed metal oxide catalyst. Catalyst was prepared by varying Ba−Zr ratios using co‐precipitation method. Various phases formed, planes exposed, morphology, elemental composition and particle size, basic site density and strength, oxidation state of elements were well studied by using various characterization techniques. The XRD analysis clearly indicates the presence of Ba+2 and Zr+4 in the form of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It is noteworthy that isomerization in an organic or an aqueous–organic solvents resulted for most of solid bases in worse isomerization rates and yields compared to aqueous phase. Thus, H 2 O-DMSO, , H 2 O-THF (THF = tetrahydrofuran), H 2 O-DMF, , H 2 O-DMA (DMA = dimethylacetamide), H 2 O-sulfolane, H 2 O-acetone, H 2 O-methanol, , and H 2 O-ethanol, mixtures were exploited. In addition, pure DMA, DMF, ,,, DMSO, , methanol, ,,, ethanol, ,,, 1-propanol, iso-propanol, , 1-butanol, 2-butanol, γ-valerolactone (GVL), toluene, and sulfolane were tested.…”
Section: Isomerization In the Presence Of Solid Catalystsmentioning
confidence: 99%
“…It is noteworthy that isomerization in an organic or an aqueous–organic solvents resulted for most of solid bases in worse isomerization rates and yields compared to aqueous phase. Thus, H 2 O-DMSO, , H 2 O-THF (THF = tetrahydrofuran), H 2 O-DMF, , H 2 O-DMA (DMA = dimethylacetamide), H 2 O-sulfolane, H 2 O-acetone, H 2 O-methanol, , and H 2 O-ethanol, mixtures were exploited. In addition, pure DMA, DMF, ,,, DMSO, , methanol, ,,, ethanol, ,,, 1-propanol, iso-propanol, , 1-butanol, 2-butanol, γ-valerolactone (GVL), toluene, and sulfolane were tested.…”
Section: Isomerization In the Presence Of Solid Catalystsmentioning
confidence: 99%
“…[17] Recently, some heterogeneous catalysts have been attracted owing to the advantages of reusability and easy separation from the reaction system. Many solid base catalysts such as metal oxides, [18][19][20] solid organic amines polymer [21][22] and mesoporous molecular sieves [23][24] were used as catalysts for isomerization of glucose. Chadwick et al investigated the isomerization of glucose catalyzed by magnesium doped NaY molecular sieves and found that although the conversion of glucose increased with the increase of magnesium content, the selectivity of fructose significantly decreased, the 44.6 % conversion of glucose with 72.7 % selectivity of fructose was reached in the 10 wt% Mg-impregnated NaY catalytic system at 100 °C after 2 h. [25] A natural mineral bentonite was used as catalyst to obtain 39.2 % yield and 86.3 % selective of fructose in high catalyst load of 167 wt% at 110 °C and 60 min.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some heterogeneous catalysts have been attracted owing to the advantages of reusability and easy separation from the reaction system. Many solid base catalysts such as metal oxides, [18–20] solid organic amines polymer [21–22] and mesoporous molecular sieves [23–24] were used as catalysts for isomerization of glucose. Chadwick et al.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the process is high cost and was restricted by the lower stability and the short life cycle of enzyme. Therefore, various efforts have been transferred to the chemical routes on glucose isomerization into fructose by screening effective catalysts [15–22] . Some homogeneous catalysts such as alkali hydroxides and organic amines have been applied for glucose isomerization in water and the yield of fructose was achieved 10–40 % with the selectivity of 40–76 %, however, these homogeneous catalysts were separated difficultly from the reaction products accompanying with strong irritant odors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various efforts have been transferred to the chemical routes on glucose isomerization into fructose by screening effective catalysts. [15][16][17][18][19][20][21][22] Some homogeneous catalysts such as alkali hydroxides and organic amines have been applied for glucose isomerization in water and the yield of fructose was achieved 10-40 % with the selectivity of 40-76 %, however, these homogeneous catalysts were separated difficultly from the reaction products accompanying with strong irritant odors. Therefore, it is essential to adopt the heterogeneous catalysts for the fructose production.…”
Section: Introductionmentioning
confidence: 99%